2012
DOI: 10.1111/jfpp.12005
|View full text |Cite
|
Sign up to set email alerts
|

Residence Time Distribution of Soy Protein Isolate and Corn Flour Feed Mix in a Twin-Screw Extruder

Abstract: The residence time distribution (RTD) of soy protein isolate (SPI) and corn flour mixture through a twin‐screw extruder under different conditions was evaluated. A full‐factorial design of experiments was used to select the variables at different levels. The feed mixture was prepared by blending corn flour and SPI in the ratio of 4:1 (20% SPI content). The effect of screw speed (75, 100 and 125 rpm), feed mixture moisture content (25, 30 and 35%) and die diameter (3 and 5 mm) were investigated. All factors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
(34 reference statements)
1
5
0
Order By: Relevance
“…However, excess moisture and a high level of hydrolysis of fish protein decreased viscosity so much that it was difficult for the material to exit the extruder (Choudhury and Gautam, 2003a). In Figure 2B, it was observed that the high screw speeds decreased the TMR, according to that reported by Yu et al (2014), presenting a more efficient heat dissipation, greater pumping force, and more significant shear, giving way to better mixing of the material and a short TMR (Kumar et al, 2006). A drop in TMR was observed at extreme temperatures and slightly increased when the process was at intermediate temperatures.…”
Section: Retention Mean Time (Tmr)supporting
confidence: 59%
“…However, excess moisture and a high level of hydrolysis of fish protein decreased viscosity so much that it was difficult for the material to exit the extruder (Choudhury and Gautam, 2003a). In Figure 2B, it was observed that the high screw speeds decreased the TMR, according to that reported by Yu et al (2014), presenting a more efficient heat dissipation, greater pumping force, and more significant shear, giving way to better mixing of the material and a short TMR (Kumar et al, 2006). A drop in TMR was observed at extreme temperatures and slightly increased when the process was at intermediate temperatures.…”
Section: Retention Mean Time (Tmr)supporting
confidence: 59%
“…Legumes such as soybean are rich source of protein. Soybean in different forms (Bookwalter, Mustakas, Kwolek, Mcghee, & Albrecht, ; Chiang, ; Iwe et al, ; Lobato, Anibal, Lazaretti, & Grossmann, ; Singh & Muthukumarappan, ; Yu, Meng, Ramaswamy, & Boye, ) have been extensively used as a major ingredient during extrusion.…”
Section: Introductionmentioning
confidence: 99%
“…The pressures in these barrels is between 1 and 4 MPa in HMEC and up to 13 MPa in LMEC 35 37 . Yu et al 38 showed in different LMEC settings fastest particle residence times (first signs of the tracer) from 10 to 40 s and extrudate collection times (complete tracer passed) from 60 to 120 s, resulting in mean residence times of 35–87 s, depending on feed moisture, screw speed and die diameter. So far it is described that vegetative forms of bacteria are inactivated effectively by this process and only spores of bacteria like Bacilli and Clostridia would survive the extrusion process 39 , 40 .…”
Section: Discussionmentioning
confidence: 99%